FENOMENA BALAPAN MOTOR : (Studi Kasus Pada Jalan Tilung XIII Kota Palangka Raya) - Meymit Pramita (Prodi Sosiologi FISIP UPR, 2019)
This study aims to find out how the phenomenon of motorbike racing on Tilung XIII road and find out the influence causes of teenagers doing motor racing on Tilung XIII road. This research method uses qualitative descriptive approach and data collection techniques namely observation, interviews and documentation. Qualitative research methods are research methods that describe and describe the symptoms that occur so that they can be used as material to answer the problems studied. To get data and information, the researcher uses observation and interview techniques. From observations and interviews, the researchers got 7 informants after collecting data from the results of research data analysis techniques conducted at the time of the research, namely data reduction data presentation and conclusions. The results of the study were that the phenomenon of motor racing was carried out by a group of teenagers on Tilung XIII street, a collection of teenagers who conduct motorbike races on Tilung XIII street have a great influence on other teenagers to imitate and take part in the race actions that are carried out. motorbike races are held in public places and in addition to colliding with speed the place also often causes commotion such as frequent brawls. Based on the discussion that has been explained that the factors that most influence adolescents to do motorbike racing is the factor of lack of affection from the family or parents of adolescents because in times of growth towards maturity parents should be the main person to give a sense of attention and affection towards adolescents and the influence of friends is also very influential in influencing adolescents entering motor racing as well as a lack of control from the police.